Impact of Digital Transformation in Educational Management: A Study on Teacher Training and Student Engagement - Makinde , Bukola Olawumi; Onasanya, Hafsat Ibironke (Interdisciplinary Journal Of Lifelong Learning, 2025)
The widespread presence of digital tools prompts important inquiries on the magnitude of this change and its subtle impacts on teacher training and student engagement. This study examines the impact of digital transformation in educational management focusing on teacher training and student engagement at Lagos State University, Ojo, Lagos State, Nigeria. The study employed a descriptive survey design to assess the impact of digital transformation on teacher training and student engagement. The population for this study consists of 250 participants, including faculty members and students from Lagos State University, Ojo, Lagos State, Nigeria. A stratified random sampling technique was used to ensure representation across different departments and faculties selected for the study. Data were collected using a structured questionnaire designed to measure the variables of interest: digital transformation, teacher training, and student engagement. The questionnaire was validated through expert review and a pilot test, achieving a reliability coefficient (Cronbach’s alpha) of 0.85. The questionnaires were administered to the selected participants via face-to-face methods to maximize response rates. The finding shows the Pearson correlation coefficients for the relationships between digital transformation, teacher training, and student engagement. The results indicate significant positive correlations between digital transformation and both teacher training (r = 0.68, p < 0.05) and student engagement (r = 0.72, p < 0.05). Conclusively, this study highlights the significant role of digital transformation initiatives in enhancing teacher training and promoting student engagement within the educational management framework in Lagos State, Nigeria. Recommendations are made for policymakers and educational leaders to prioritize digital training for teachers and develop strategies to improve student engagement through technology